The Roles of Departmental and Position Power in Job Evaluation - Welbourne, Theresa M.; Trevor, Charlie O. (Academy of Management Journal, 2000)
Applying macro-level research on power and resource allocation to job evaluation in a university setting, the authors tested whether job evaluation outcomes were affected by departmental power. They found that departmental power had a positive effect on the number of a department's new positions and position upgrades that were authorized at the requested pay grade levels. Additionally, the authors considered power at the individual level of analysis and found that the effects of departmental power on new positions and position upgrades were greater when the position power of resource recipients was high.